Annual survival probabilities of juvenile loggerhead sea turtles indicate high anthropogenic impact on Mediterranean populations. Issue 5 (20th May 2014) - Casale, Paolo; Freggi, Daniela; Furii, Giovanni; Vallini, Carola; Salvemini, Pasquale; Deflorio, Michele; Totaro, Giovanni; Raimondi, Stefano; Fortuna, Caterina; Godley, Brendan J.
Abstract One of the major gaps in the knowledge of sea turtle population dynamics is survival probability, in particular of juveniles, which represent the bulk of the population and whose survival has the greatest effect on population growth. One of the major global threats to sea turtles is incidental bycatch, although not all animals die in the process. This is particularly acute for the loggerhead sea turtle (Caretta caretta). Here fisheries‐dependent monitoring is used to seek insights into patterns of survival at multiple Mediterranean foraging areas: north and south Adriatic, north Ionian, and the Tunisian shelf. Annual survival probability was estimated using the catch curve method. Size data of 2191 loggerhead turtles ranging from 19 to 92 cm curved carapace length were converted to age according to eight age–size curves available from the Mediterranean Sea. The mean annual survival probabilities for the four areas were heterogeneous and ranged between 0.710 and 0.862. Results suggest that the survival probabilities for Mediterranean loggerheads, especially in some areas, are lower than would be expected from a healthy population. This is of particular concern for the Greek rookeries, which appear most affected by anthropogenic mortality occurring in the study areas. This supports the implementation in those areas of measures mitigating the main threats, notably bycatch. Copyright © 2014 John Wiley & Sons, Ltd.